Translating Research to Practice Using a Team-Based Approach to Cancer Rehabilitation: A Physical Therapy and Exercise-Based Cancer Rehabilitation Program Reduces Fatigue and Improves Aerobic Capacity. Issue 4 (October 2018) - Leach, Heather J.; Covington, Kelley R.; Pergolotti, Mackenzi; Sharp, Julia; Maynard, Brooke; Eagan, Jeffrey; Beasley, Joanne
Abstract : Background and Objective: Intervention research has shown that exercise-based rehabilitation is safe and effective for reducing disease burden across the cancer continuum. However, the translation of this research to programs implemented in health care settings remains a challenge. This study describes the implementation of a physical therapy–based exercise program for patients who have been diagnosed with cancer and its effectiveness for reducing fatigue and improving aerobic capacity. Methods: Retrospective analysis of a single-group, pre/postprogram assessment for adult patients who have been diagnosed with cancer (N = 546). Six-Minute Walk Test (6MWT) measured aerobic capacity. Functional Assessment of Chronic Illness Therapy–Fatigue (FACIT-Fatigue) and Piper Fatigue Scale (PFS) measured fatigue. Paired-samples t tests examined changes in outcomes from pre- to postprogram assessments. Linear regression explored predictors of postprogram outcomes. Results: Participants were 63.7 ± 12.2 years old, diagnosed with breast (27.1%), hematological (15.4%), head and neck (12.6%), lung (12.3%), prostate (11%), colorectal (7.3%), or other (14.3%) cancers. For those who completed the postprogram measures (N = 169), FACIT-Fatigue scores improved ( M Δ = +8.42 ± 9.2, t 79 = −8.21, P = .000), PFS scores improved ( M Δ = −2.1 ± 2.0, t 81 = 9.5, P = .000), and 6MWT distance improved ( M Δ = +42.9 ± 53.8 m, t 160 = −10.1, P = .000). Age ( P = .034) and time since completing chemotherapy ( P = .000) or radiation therapy ( P = .014) was inversely associated with the 6MWT. Greater exercise session attendance was associated with higher PFS scores ( P = .020). Limitations: Only 31% of participants completed postprogram assessments, and limited information was available regarding reasons for dropout/withdrawal. Conclusions: This study provides a real-world example of a cancer rehabilitation program implemented in a health care setting, which was successful in reducing fatigue and improving aerobic capacity.